Volumetric analysis of the terminal ductal lobular unit architecture and cell phenotypes in the human breast - Paavolainen, Oona; Peurla, Markus; Koskinen, Leena M.; Pohjankukka, Jonna; Saberi, Kamyab; Tammelin, Ella; Sulander, Suvi-Riitta; Valkonen, Masi; Mourao, Larissa; Boström, Pia; Brück, Nina; Ruusuvuori, Pekka; et al. (Cell Press, 2025)
The major lactiferous ducts of the human breast branch out and end at terminal ductal lobular units (TDLUs). Despite their functional and clinical importance, the three-dimensional (3D) architecture of TDLUs has remained undetermined. Our quantitative and volumetric imaging of healthy human breast tissue demonstrates that highly branched TDLUs, which exhibit increased proliferation, are uncommon in the resting tissue regardless of donor age, parity, or hormonal contraception. Overall, TDLUs have a consistent shape and branch parameters, and they contain a main subtree that dominates in bifurcation events and exhibits a more duct-like keratin expression pattern. Simulation of TDLU branching morphogenesis in three dimensions suggests that evolutionarily conserved mechanisms regulate mammary gland branching in humans and mice despite their anatomical differences. In all, our data provide structural insight into 3D anatomy and branching of the human breast and exemplify the power of volumetric imaging in gaining a deeper understanding of breast biology.